Livro didático como inimigo social: análise retórica de peças judiciais do ano de 2017 do município de Ariquemes-RO - Chediak, Taiane Cortez de Souza (2021)
This research comprehends a study of lawsuits about a textbook adoption filed in the municipality of Ariquemes-RO, in 2017. The main objective is to analyze the rhetoric of lawsuits. From that, we intended to: a) investigate how rhetoric was developed concerning the textbook involved in the court proceedings; b) identify the rhetorical elements in court proceedings involving the textbook; c) describe persuasion and fear rhetorical arguments in speeches regarding the textbook in court proceedings. The methodological procedures characterize this research as a case study with a qualitative approach. As for the purposes, the research is exploratory and uses rhetorical analysis as an analysis procedure, consisting of legal pieces produced in 2017, with a public civil action and a court decision, on the textbook in the municipality of Ariquemes-RO. The theoretical framework is based on rhetoric, more specifically on the rhetoric of fear and conviction. This study is extremely relevant, considering that it reveals rhetorical constructions of mass manipulation in relation to the textbook. With this, we intend to demonstrate the consequences for the use of the textbook, both in the technical-scientific production supported by science and knowledge, and, through rhetorical analysis, in confrontations triggered by polarized political disputes